A stable room-temperature sodium–sulfur battery - Wei, Shuya (Nat Commun, 2016)
High-energy rechargeable batteries based on earth-abundant materials are important for mobile and stationary storage technologies. Rechargeable sodium–sulfur batteries able to operate stably at room temperature are among the most sought-after platforms because such cells take advantage of a two-electron-redox process to achieve high storage capacity from inexpensive electrode materials. Here we report a room-temperature sodium–sulfur battery that uses a microporous carbon–sulfur composite cathode, and a liquid carbonate electrolyte containing the ionic liquid 1-methyl-3-propylimidazolium-chlorate tethered to SiO(2) nanoparticles. We show that these cells can cycle stably at a rate of 0.5 C (1 C=1675, mAh g(−1)) with 600 mAh g(−1) reversible capacity and nearly 100% Coulombic efficiency. By means of spectroscopic and electrochemical analysis, we find that the particles form a sodium-ion conductive film on the anode, which stabilizes deposition of sodium. We also find that sulfur remains interred in the carbon pores and undergo solid-state electrochemical reactions with sodium ions.